1990
DOI: 10.1080/01140671.1990.10428093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and leaf wetness on the potato late blight

Abstract: The time required for potato late blight lesions, caused by Phytophthora infestans (Mont.) de Bary, to produce sporangia during periods of continuous leaf wetness, and for inoculations to produce lesions bearing sporangia, was determined over a temperature range of 5-24°C. Equations were derived relating time to sporulate with temperature. A 2-h break in leaf wetness, initiated at any time within the first 3 h of incubation after inoculation, markedly reduced lesion numbers. When the break was initiated later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 2 publications
1
9
0
1
Order By: Relevance
“…To our knowledge, no previous research has demonstrated the effect of temperature on late blight development on hairy nightshade. Our data shows that the optimum temperature range (18-22°C) for infection of hairy nightshade is the same as that previously reported for potato and tomato (Minogue and Fry, 1981;Hartill et al, 1990;Sato, 1994;Mizubuti and Fry, 1998;Becktell et al, 2005). Variation in RH effects on foliar incidence and late blight severity was observed in our experiments.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To our knowledge, no previous research has demonstrated the effect of temperature on late blight development on hairy nightshade. Our data shows that the optimum temperature range (18-22°C) for infection of hairy nightshade is the same as that previously reported for potato and tomato (Minogue and Fry, 1981;Hartill et al, 1990;Sato, 1994;Mizubuti and Fry, 1998;Becktell et al, 2005). Variation in RH effects on foliar incidence and late blight severity was observed in our experiments.…”
Section: Discussionsupporting
confidence: 89%
“…Due to the fact that RH conditions for late blight development are well documented for potato and tomato (Minogue and Fry, 1981;Hartill et al, 1990;Gleason et al, 1995), humidity effects were only evaluated on hairy nightshade. Six to eight-week old hairy nightshade plants were inoculated with sporangia suspension at 5 · 10 3 sporangia ⁄ ml using the 00-109, 02-1, 00-9, and 00-87 isolates.…”
Section: Effects Of Rhmentioning
confidence: 99%
“…Phytophthora infestans can cause severe damage in potato crops. Favourable circumstances are dull, not too cold weather, with long periods of leaf wetness (Harthill et al ., 1990;Harrison, 1995). During the growing season, Dutch farmers apply fungicides every 5 -7 days during favourable weather, up to 15 times a season.…”
Section: Phytophthora Infestans Models (Plant-plus and Prophy)mentioning
confidence: 99%
“…Hartill et al. () showed that sporulation time for P. infestans on potato decreases with increasing temperatures between 5 and 22°C. Becktell et al.…”
Section: Introductionmentioning
confidence: 99%
“…He further reported that infected tuber slices incubated at 18-23°C in a saturated atmosphere very commonly produce sporangia in 72 h after zoospores have been placed on them. Hartill et al (1990) showed that sporulation time for P. infestans on potato decreases with increasing temperatures between 5 and 22°C. Becktell et al (2005) found for P. infestans on Petunia that there was very little difference in time required for sporulation at temperatures between 13 and 23°C (6-9 h), but that there was a slight trend towards more rapid sporulation at 23°C on petunia and tomato.…”
Section: Introductionmentioning
confidence: 99%